2023 update of template tables for reporting biomolecular structural modelling of small‐angle scattering data. Issue 2 (10th February 2023) - Trewhella, Jill; Jeffries, Cy M.; Whitten, Andrew E.
Abstract : An updated template reporting table based on the 2017 publication guidelines for biomolecular SAS and 3D modelling is presented that includes standard descriptions for proteins, glycosylated proteins, DNA and RNA, and some reorganization of the data to improve readability and interpretation. A specialized template has also been developed for reporting SAS contrast‐variation data and models that incorporates the additional reporting requirements for these more complicated experiments. Abstract : In 2017, guidelines were published for reporting structural modelling of small‐angle scattering (SAS) data from biomolecules in solution that exemplified best‐practice documentation of experiments and analysis. Since then, there has been significant progress in SAS data and model archiving, and the IUCr journal editors announced that the IUCr biology journals will require the deposition of SAS data used in biomolecular structure solution into a public archive, as well as adherence to the 2017 reporting guidelines. In this context, the reporting template tables accompanying the 2017 publication guidelines have been reviewed with a focus on making them both easier to use and more general. With input from the SAS community via the IUCr Commission on SAS and attendees of the triennial 2022 SAS meeting (SAS2022, Campinas, Brazil), an updated reporting template table has been developed that includes standard descriptions for proteins, glycosylated proteins, DNA and RNA, with some reorganization of the data to improve readability and interpretation. In addition, a specialized template has been developed for reporting SAS contrast‐variation (SAS‐cv) data and models that incorporates the additional reporting requirements from the 2017 guidelines for these more complicated experiments. To demonstrate their utility, examples of reporting with these new templates are provided for a SAS study of a DNA–protein complex and a SAS‐cv experiment on a protein complex. The examples demonstrate how the tabulated information promotes transparent reporting that, in combination with the recommended figures and additional information best presented in the main text, enables the reader of the work to readily draw their own conclusions regarding the quality of the data and the validity of the models presented.